Technological aspects of obtaining liquid extracts of black poplar buds and determining the strategy for their standardization at the pharmaceutical development stage - Bondar, Anna; Gubar, Svitlana; Smielova, Nataliia; Shyteyeva, Tatyana; Tkachenko, Olena; Kryvoruchko, Liliia; Karpenko, Karina; Georgiyants, Viktoria (ScienceRise: Pharmaceutical Science, 2020)
The aim. Conducting research on the development of technology for obtaining liquid extract of poplar black buds, their standardization and determining the optimal parameters of the technological process of extraction, which should provide the required content of biologically active substances and pharmacological activity of the drug. Methods. The production of liquid extracts was carried out by the method of percolation. The quantitative determination of the amount of hydroxycinnamic acid derivatives was carried out by the unified spectrophotometric method recommended by the State Pharmacopoeia of Ukraine, in terms of coffee acid, at an analytical wavelength of 509 ± 3 nm. To determine the quantitative content of the sum of flavonoids was used the method of differential spectrophotometry, flavonoids were calculated in terms of luteolin, by the reaction of flavonoids with a 2 % solution of aluminium chloride in ethanol (96 %) R at an analytical wavelength of 398 ± 3 nm. Results. The research on the technology of obtaining liquid extracts of black poplar buds was carried out. The technological parameters of the crushed medicinal plant raw material of the black poplar buds (bulk, the coefficient of filling of the dry raw material) were determined and the extraction parameters were calculated. It is established that the process requires the use of 2nd and 3rd discharges, and returns them to the process at the first stage of the process for the series that follows. To increase the absolute content of biologically active substances, it is rational to change the extraction regimes (infusion time, extractant flow rate, temperature). The quantitative determination of extractive substances and spectrophotometric determination of the amount of hydroxycinnamic acid derivatives in terms of coffee acid, as well as the amount of flavonoids in terms of luteolin at all stages of the process of obtaining liquid extracts was done. The influence of the concentration of the extractant on the qualitative composition of the obtained extract was established. The optimal extraction conditions were selected and the technology for ethanol extracts based on ethanol (96 %) R and ethanol (70 %) R was developed from medicinal plant material of black poplar buds. To increase the absolute content of biologically active substances in liquid extracts experimentally argued to increase the infusion time to 24 hours. The liquid extracts of black poplar buds have been developed for their further screening studies. Conclusions. As a result of the study was developed the technology of obtaining liquid extracts of poplar black buds, their standardization was carried out, the optimal parameters of the technological extraction process were determined, ethanol extracts were developed for their further screening studies